Variability in multiple paternity rates for grey reef sharks (Carcharhinus amblyrhynchos) and scalloped hammerheads (Sphyrna lewini) - M. E. Green (Nature Portfolio, 2017)
Abstract This study assessed the presence and prevalence of multiple paternity (MP) in litters of grey reef sharks (Carcharhinus amblyrhynchos) and scalloped hammerheads (Sphyrna lewini) opportunistically caught in Papua New Guinea (PNG). Litter size between species were significantly different with an average of 3.3 pups for grey reef sharks and 17.2 pups for scalloped hammerhead. Using 14 and 10 microsatellite loci respectively, we identified MP in 66% of grey reef sharks (4 out of 6 litters) and 100% MP in scalloped hammerheads (5 litters). We found high paternal skew (the uneven contribution of sires per litter) and a positive correlation between female adult size and litter size in scalloped hammerheads but not in grey reef sharks. Differences in the frequency of MP between species and the identification of paternal skew may be linked with mating strategies and post-copulatory mechanisms. Multiple paternity is thought to benefit populations by enhancing genetic diversity therefore increasing the population’s genetic resilience to extrinsic pressures. The identification of MP in two shark species reported here, further elucidates the complex breeding strategies elasmobranchs undertake.